Isolation and molecular detection of Streptococcus agalactiae from popped eye disease of cultured Tilapia and Vietnamese koi fishes in Bangladesh - Rahman, Mohummad Muklesur; Rahman, Md Ashikur; Monir, Md Shirajum; Haque, Md Enamul; Siddique, Mahbubul Pratik; Khasruzzaman, A K M; Rahman, Md Tanvir; Islam, Md Alimul (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Present research aims to isolate, identify, and determine the virulence of the Streptococcus agalactiae (group B Streptococcus; GBS), isolated from popped eye disease affected Tilapia and Vietnamese Koi (V. Koi) fishes. Materials and Methods: A total of 330 fish samples were collected, of which Tilapia (n = 180) and V. Koi (n = 150), were collected from 35 affected ponds of four selected districts of Bangladesh. Isolation of the bacterium was done using different culture media (Nutrient broth, Plate count agar, Tryptic Soy Agar, and Blood agar), and identification by using various biochemical tests (conventional and using API 20 Strep kit) and polymerase chain reaction (PCR) using primers against 16S rRNA gene of S. agalactiae. Antibiotic susceptibility of the bacteria was performed using seven different antibiotics disc (Tetracycline, Oxytetracycline, Chlortetracycline, Streptomycin, Ciprofloxacin, Gentamicin, and Neomycin). Virulence of the isolated S. agalactiae was determined by infecting healthy Tilapia and V. Koi fishes through experimental infection. Results: Isolated bacteria were found Gram-positive paired and chained cocci, β-hemolytic and non-motile. Findings of biochemical and serological tests indicate that the isolated bacterium belongs to Group B Streptococcus of Lancefield classification. PCR result also confirmed that the bacteria were S. agalactiae. The bacterial isolates possessed resistance property against all the seven antibiotics used in this study. The isolated GBS was found highly virulent and showed 80%–90% mortality for Tilapia and V. Koi fishes in experimental infection within 1–6 days of post-infection. Conclusion: From the findings of this study, it may be concluded that isolated GBS from the Tilapia and V. Koi fishes were highly virulent and possessed multidrug-resistance properties. J. Adv. Vet. Anim. Res., 8(1): 14-23, Mar 2021 http://doi.org/10.5455/javar.2021.h480